2013
DOI: 10.1021/om4000067
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Catalytic Studies of Palladium and Platinum Bis-Sulfoxide Complexes

Abstract: The bis-sulfoxide ligand p-tolyl-binaso and its derivatives can be used to synthesize neutral and cationic palladium and platinum complexes. Various Pt bis-sulfoxide complexes could be made by using the precursor Pt(M,SS,SS)-p-tolyl-binasoCl2 (5a) and abstracting the chlorides with silver salts. The Pd analogue of this compound (4) could not be used in the same way. In this case, the sulfoxides appear to be very weakly coordinated and different methods to make stable Pd bis-sulfoxide complexes had to be found.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 82 publications
1
14
0
Order By: Relevance
“…Palladium and platinum complexes of the bissulfoxide ligand p-tolyl-binaso (see also later discussions) was synthesised in the Dorta group. 65 It was found that in the cationic complex, 33, the 80 ligand was coordinated in a cis-κ 2 -S,O fashion (Figure 17). These studies also revealed that the trans effect of other ligands in Ptbinaso complexes determine the labilitity of the metal-sulfoxide bond.…”
Section: Bissulfoxide Metal Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Palladium and platinum complexes of the bissulfoxide ligand p-tolyl-binaso (see also later discussions) was synthesised in the Dorta group. 65 It was found that in the cationic complex, 33, the 80 ligand was coordinated in a cis-κ 2 -S,O fashion (Figure 17). These studies also revealed that the trans effect of other ligands in Ptbinaso complexes determine the labilitity of the metal-sulfoxide bond.…”
Section: Bissulfoxide Metal Complexesmentioning
confidence: 99%
“…88 The groups of Bäckvall and Larock further explored the scope of this catalytic system, finding it could be successfully applied to other oxidative cyclisations 89 and the conversion of enol silanes to enones and enals. 90 The reason this catalytic system was successful was still 65 unclear at that point, although it had been speculated that Pd clusters were responsible for the catalysis. To investigate this theory, Speckamp and co-workers performed TEM imaging on typical reaction solutions and observed that Pd clusters were indeed present.…”
Section: Palladium Dmso Systems In Catalysismentioning
confidence: 99%
“…For example, the bis-sulfoxide derivatives are used as ligands in the stabilisation of transition metal or lanthanide complexes or as ligand in transition metal-catalyzed reactions or in various catalytic processes. [5,7,[9][10][11][12][13][14][15][16][17][18] In most of the cases the coordination to the metal center is realized through the sulfur atom of the sulfinyl group, [5,11,14,15,[18][19][20][21][22][23] however, coordination through the oxygen atom is also a possibility, some examples are presented in the literature. [12,14,[23][24][25][26] The synthesis of the sulfoxides can be realized by different methods such as the arylation of sulfenate anions by a coupling reaction, a nucleophilic substitution or an electrophilic attack, with the formation of a C-SO bond, [27][28][29][30][31] or by oxidation of a sulfide through a thioether as intermediary derivative.…”
Section: Introductionmentioning
confidence: 99%
“…Derivatives containing two sulfinyl groups with different roles, in the chemical processes are also known. For example, the bis‐sulfoxide derivatives are used as ligands in the stabilisation of transition metal or lanthanide complexes or as ligand in transition metal‐catalyzed reactions or in various catalytic processes , , . In most of the cases the coordination to the metal center is realized through the sulfur atom of the sulfinyl group,, , , , however, coordination through the oxygen atom is also a possibility, some examples are presented in the literature , , …”
Section: Introductionmentioning
confidence: 99%
“…For instance, papers making extraordinary claims with less than convincing evidence are often forced-sometimes unwillingly-into the spotlight (e.g., cells living without phosphorus [Reaves et al, 2012;Wolfe-Simon et al, 2011]; mitochondria as a link to the soul [Warda and Han, 2008]; dubious links to genetically modified corn and cancer in rats [Sé ralini et al, 2012]). Worrying signs can go viral, like embarrassing notes coauthors left for each other that they failed to take out of the manuscript (''for this compound, just make up an elemental analysis,'' from supplemental material in Drinkel et al, 2013). We've all read papers and asked, ''How did this get published?''…”
mentioning
confidence: 99%